Key Factors of Undergraduate Satisfaction and Continued Use of Mobile Shopping Apps in Yibin, China - Wenli, Zeng (Scholar: Human Sciences, 2025)
Purpose: This paper aims to examine the significant impact of key factors of mobile shopping applications on satisfaction and intention to reuse among university students in Yibin, China. The conceptual framework presented the cause and effect among information quality, system quality, savings, intention to reuse, satisfaction, trust, and perceived usefulness relation. Research Design, Data, and Methods: The researchers used quantitative techniques (n=500) to conduct a questionnaire survey among students at Sichuan University of Science & Engineering in Yibin, China. Non-probability sampling includes judgment sampling to select computer science students, quota sampling to determine sample size, and convenience sampling to collect data and distribute questionnaires online and offline. The researchers used structural equation modeling (SEM) and confirmatory factor analysis (CFA) for data analysis, including model fit, reliability, and construct validity. Results: The results show that perceived usefulness and information quality significantly impact satisfaction, and satisfaction is used as an intermediate variable to influence students' mobile shopping intention to reuse. Each exogenous variable demonstrated a significant impact on the related endogenous variables, with Perceived usefulness and Information quality significantly impacting mobile shopping application usage satisfaction. Perceived usefulness greatly impacts mobile shopping application usage satisfaction, followed by Information quality and savings. Conclusion: Policymakers and program operators can increase the impact of factors on students' perceived ease of use and savings in mobile shopping applications. Investment and optimize the investment ratio.